Analisis Sebaran Puskesmas Untuk Peningkatan Pelayanan Kesehatan Dengan Metode Fuzzy C-Means - Siska Kurnia Gusti (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Analytical determination of the distribution centers in Kampar regency is necessary to determine whether or not to increase health services in the area. The data required is the total population, area, health workers and the existing facilities and infrastructures. The search process undertaken to generate information about the distribution of health centers and better with less categories. Pengkatagorikan distribution centers, of course there are the criteria for distribution centers that have an uncertain value. Therefore, to address the criteria that have an uncertain value may use the approach to fuzzy clustering models. This clustering model is known as Fuzzy Clustering Means (FCM). So the end result can be obtained by the data distribution centers are needed.Keywords: Analysis, FCM, Criteria, Health Center